2021
DOI: 10.3389/fimmu.2021.661939
|View full text |Cite|
|
Sign up to set email alerts
|

NLRP3 Inflammasome Promotes the Progression of Acute Myeloid Leukemia via IL-1β Pathway

Abstract: NLRP3 inflammasome has been reported to be associated with the pathogenesis of multiple solid tumors. However, the role of NLRP3 inflammasome in acute myeloid leukemia (AML) remains unclear. We showed that NLRP3 inflammasome is over-expressed and highly activated in AML bone marrow leukemia cells, which is correlated with poor prognosis. The activation of NLRP3 inflammasome in AML cells promotes leukemia cells proliferation, inhibits apoptosis and increases resistance to chemotherapy, while inactivation of NLR… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 51 publications
(103 reference statements)
0
22
0
Order By: Relevance
“…Inflammasomes’ contribution to acute myeloid leukemia (AML) is currently the most extensively studied among all hematological diseases. The NLRP3 inflammasome is highly activated and overexpressed in AML cells [ 40 , 41 ]. Bone marrow mononuclear cells (BMMNCs) obtained from newly diagnosed AML patients showed markedly elevated expression of the NLRP3 pathway; however, the results for specific components varied between the studies.…”
Section: Leukemiasmentioning
confidence: 99%
See 2 more Smart Citations
“…Inflammasomes’ contribution to acute myeloid leukemia (AML) is currently the most extensively studied among all hematological diseases. The NLRP3 inflammasome is highly activated and overexpressed in AML cells [ 40 , 41 ]. Bone marrow mononuclear cells (BMMNCs) obtained from newly diagnosed AML patients showed markedly elevated expression of the NLRP3 pathway; however, the results for specific components varied between the studies.…”
Section: Leukemiasmentioning
confidence: 99%
“…Bone marrow mononuclear cells (BMMNCs) obtained from newly diagnosed AML patients showed markedly elevated expression of the NLRP3 pathway; however, the results for specific components varied between the studies. Depending on the information source, upregulation of NLRP3, ASC, caspase-1, IL-18, and IL-1β transcripts were reported [ 40 , 41 ]. In peripheral blood mononuclear cells (PBMCs), ASC and IL-18 mRNA levels were significantly upregulated [ 41 ].…”
Section: Leukemiasmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, the role of NLRP3 inflammasome in the pathogenesis of AML is not well documented. Zhong et al showed that AML cells overexpressed NLRP3 inflammasome components and the NRLP3 inflammasome assisted in AML propagation in an IL-1β dependent manner [ 132 ]. The same authors also demonstrated immunological implications of the NLRP3 inflammasome, which is associated with an aryl-hydrocarbon receptor (AHR) contributed to AML T helper cell abnormalities [ 133 ].…”
Section: Immune Evasion In Acute Myeloid Leukemiamentioning
confidence: 99%
“…A recent study showed that NLRP3 inflammasome promotes AML progression in an IL-1β-dependent manner. In patient-derived samples, NLRP3 was overexpressed and highly activated in AML bone marrow leukemia cells, and this correlated with poor prognosis, and the activation of NLRP3 in AML cells promoted leukemia cell proliferation, inhibited apoptosis, and increased resistance to chemotherapy [19].…”
Section: Nlrp3 In Hematopoiesis and Leukemogenesismentioning
confidence: 99%